Vitamin D As Predictive Biomarker In The Severity of Acne Vulgaris: A Systematic Review - Dewi, Merly Purnama; Sari, Ida Ayu Diah Purnama; Wiratama, Bayu Kresna; Rahmayani , Irma (Jurnal Locus Penelitian dan Pengabdian, 2026)
This systematic review aims to evaluate differences in serum vitamin D levels between individuals with acne vulgaris and healthy individuals and to assess whether vitamin D levels can serve as a predictive biomarker for the severity of acne vulgaris. A systematic search was conducted using Publish or Perish, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, in Scopus, PubMed, Semantic Scholar, and SINTA databases. Eligible studies involved participants aged 12–59 years from Asia and Africa. Nine studies met the criteria, including 1,212 participants (655 with acne vulgaris and 557 healthy controls). The methodological quality of each included study was assessed using the Newcastle-Ottawa Scale (NOS), covering selection, comparability, and outcome domains. Most studies reported lower serum vitamin D levels in acne patients than in controls. Six studies showed a significant inverse correlation with acne severity, while three found no significant correlation, possibly due to influencing factors such as sun exposure, diet, supplements, and lifestyle. Although most studies indicate a significant inverse relationship between serum vitamin D levels and acne severity, the absence of predictive models and statistical validation prevents vitamin D from being established as a clinical predictive biomarker. Further prospective research employing validated predictive tools is required to confirm its role in acne management.